How does climate exacerbate root causes of conflict in Zimbabwe? An econometric analysis - Victor, Villa; Belli, Anna; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Zimbabwe, using a two-stage econometric approach. The findings suggest that household and in particular children are considerably vulnerable to different kind of climate anomalies. At the district level, results show a positive correlation between level of food insecurity, climate and intensity of conflict, more specifically protest and riots.